Acute Respiratory Distress Syndrome Caused by Human Adenovirus in Adults: A Prospective Observational Study in Guangdong, China - Wu, Zhan; Zhang, Rong; Liu, Dongdong; Liu, Xuesong; Zhang, Jierong; Zhang, Zhihui; Chen, Sibei; He, Weiqun; Li, Yimin; Xu, Yonghao; Liu, Xiaoqing (Frontiers in Medicine, 2022)
Background: Viral causes of acute respiratory distress syndrome (ARDS) are mostly limited to influenza. However, adenovirus has been emerging as a cause of ARDS with a high mortality rate and described in adults are rare. Methods: We conducted a prospective, single-center observational study of viral pneumonia with ARDS and confirmed adenovirus-associated ARDS in adults at our quaternary referral institution between March 2019 and June 2020. We prospectively analyzed clinical characteristics, laboratory test results, radiological characteristics, viral load from nasopharyngeal swabs and endotracheal aspirates, treatments, and outcomes for the study participants. Results: The study enrolled 143 ARDS patients, including 47 patients with viral pneumonia-related ARDS, among which there were 14 adenovirus-associated ARDS patients, which accounted for 29.79% of the viral pneumonia-related ARDS cases. Among the adenovirus-associated ARDS patients, 78.57% were men with a mean age of 54.93 ± 19.04 years, younger than that of the non-adenovirus associated ARDS patients. Adenovirus-associated ARDS patients had no specific clinical characteristics, but they presented with decrease in the number of CD3+CD4+ T cells and higher serum creatinine during the early stage. The viral load and the positivity rate in the lower respiratory tract were higher than that of the upper respiratory tract in the patients with adenovirus-associated ARDS. All patients required invasive mechanical ventilation treatment. The average time from shortness of breath to the application of invasive ventilation was 24 hours. Ten patients (71.43%) complicated by acute kidney injury, while 13 patients (71.43%) in the non-adenovirus associated ARDS group (P = 0.045). Additionally, 85.71% of the 14 adenovirus-associated ARDS patients survived. No significant differences were detected between the two groups regarding duration of ventilation, length of ICU stay and mortality. Conclusion: Adenovirus infection is an important cause of virus-related ARDS. The positivity rate of adenovirus infection in lower respiratory tract secretions was higher than that in upper respiratory tract secretions in these patients. Age, lower CD3+CD4+ T cells, and high serum creatinine may be were associated with adenovirus induce ARDS in adults required mechanical ventilation. Early identification and intervention to prevent disease progression are essential for reducing the mortality rate in these patients.